Configurable Version Management Hardware Transactional Memory for Multi-processor Platform - Jeevan Sirkunan; Chia Yee Ooi; N. Shaikh Husin; Yuan Wen Hau; Trias Andromeda; M. N. Marsono (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Programming on a shared memory multi-processor platforms in an efficient way is difficult as locked based synchronization limits the efficiency. Transactional memory (TM) is a promising approach in creating an abstraction layer for multi-threaded programming. However, the performance of TM is application-specific. In general, the configuration of a TM is divided into version management and conflict management. Each scheme has its strengths and weaknesses depending on executing application. Previous TM implementations for embedded system were built on fixed version management configuration which results in significant performance loss when transaction behaviour changes. In this paper, we propose a hardware transactional memory (HTM) with interchangeable version management. Random requests at different contention levels are used to verify the performance of the proposed TM. The proposed architecture is targeted for embedded applications and is area-efficient compared to current implementations that apply cache coherence protocols.